Presence of intimate family and cancer screening behavior: a cross-sectional study of 4237 workers. (13th November 2019) - Miyamatsu, N; Shima, A; Morino, A; Azuma, S; Ichikawa, M; Godai, K; Kawatsu, Y; Nishikawa, T; Tanaka, H; Okamura, T
Abstract: Background: Presence of intimate family is considered as one of the related factors of health behaviors. The study aim was to clarify the relationship between the presence of significant others and having a colorectal cancer screening. Methods: This study used data of baseline survey of intervention study regarding breast cancer screening at worksites. A total of 6827 workers, aged 40 and over of the retail company, were required to fill out a self-administrated questionnaire related to cancer screening. the intimate family was defined as a person's spouse or partner and children. Logistic regression analyses were performed to estimate odds ratios [ORs] and 95% confidence intervals [CIs] of undergoing an annual screening for colorectal cancer by the presence of spouse or partner adjusting for age. The same analysis was performed regarding the presence of children. Results: Response rates were 70% in men and 71% in women. After excluding participants with a past history of cancer and lack of information about colorectal cancer screening or the presence of significant others, 4203 remained for the analyses. A total of 1777 participants reported that they had undergone screening for colorectal cancer within a year (42% in men and 42% in women). Screening rates of participants with/without a spouse were 45% and 30% in men, 44% and 38% in women. Screening rates of participants with/without children were 45% and 33% in men, 43% and 38% in women. ORs of undergoing annual colorectal cancer screening by the presence of spouse were 1.8 (1.3-2.5) in men and 1.3 (1.1-1.5) in women. ORs by the presence of children were 1.6 (1.2-2.1) in men and 1.1 (0.9-1.3) in women. Conclusions: This study indicated that health behavior in cancer screening could be affected by having a spouse in both men and women. The presence of children positively related in men. Male workers with children might be under some pressure to keep their health, from a sense of responsibility of main income earner. Key messages: Health behavior in cancer screening could be affected by having a spouse. Health behavior in cancer screening could be affected by having a child only in men.